2021
DOI: 10.1021/acsanm.1c01242
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Composition of PdAuCu Ternary Alloy Nanoparticles for Plasmonic Hydrogen Sensing

Abstract: Alloying is a long-standing central strategy in materials science for the tailoring and optimization of bulk material properties, which more recently has started to find application also in engineered nanomaterials and nanostructures used in, among other, nanoplasmonic hydrogen sensors. Specifically, alloying Pd nanoparticles to form binaries and ternaries with the coinage metals Au and Cu has proven efficient to mitigate hysteresis in the sensor response, improve response and recovery times, boost sensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…These optical properties are dominated by the localized surface plasmon resonance (LSPR), which is highly sensitive to the size, shape, and composition of the NPs, as well as the environment surrounding them. This exceptional tunability of the optical response has led to the attempted use of plasmonic NPs in a variety of applications. Successful examples range from life sciences to catalysis and bio/gas sensing and involve a large variety of metal or semiconducting NPs with different shapes, sizes, and compositions, obtained with different synthesis techniques. In the previous decade, there has also been increasing interest in improving the ability to customize the properties of NPs by combining multiple metals and oxides, either by linking together multiple single-metal NPs or by alloying the metals at the atomic level to form alloyed NPs. To this end, the combination of noble metals with other elements can create increased reactivity for catalysis and introduce significant lattice strain on the atomic scale, which has positive implications for both catalysis and sensing. Accordingly, there are numerous successful applications of alloyed NPs, including the use of gold–silver (AuAg) alloyed NPs for the sensing of various organic and biological compounds and the use of palladium–gold (PdAu), palladium–silver (PdAg), and even palladium–gold–copper (PdAuCu) NPs , for hydrogen (H 2 ) sensing, storage, and catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…These optical properties are dominated by the localized surface plasmon resonance (LSPR), which is highly sensitive to the size, shape, and composition of the NPs, as well as the environment surrounding them. This exceptional tunability of the optical response has led to the attempted use of plasmonic NPs in a variety of applications. Successful examples range from life sciences to catalysis and bio/gas sensing and involve a large variety of metal or semiconducting NPs with different shapes, sizes, and compositions, obtained with different synthesis techniques. In the previous decade, there has also been increasing interest in improving the ability to customize the properties of NPs by combining multiple metals and oxides, either by linking together multiple single-metal NPs or by alloying the metals at the atomic level to form alloyed NPs. To this end, the combination of noble metals with other elements can create increased reactivity for catalysis and introduce significant lattice strain on the atomic scale, which has positive implications for both catalysis and sensing. Accordingly, there are numerous successful applications of alloyed NPs, including the use of gold–silver (AuAg) alloyed NPs for the sensing of various organic and biological compounds and the use of palladium–gold (PdAu), palladium–silver (PdAg), and even palladium–gold–copper (PdAuCu) NPs , for hydrogen (H 2 ) sensing, storage, and catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…The required minimum amount of Cu depended on the CO concentration in the background, and a higher CO concentration required a higher Cu content. [ 66 ] Clearly, these works show that the AuPd alloys can significantly improve the performance of the PHS, while the CuPd alloy can improve the resistance to poisoning and deactivation.…”
Section: Discussion Of Previous Workmentioning
confidence: 99%
“…Furthermore, they found that in fact the Pd 65 Au 25 Cu 10 alloy had the best compromise in terms of hysteresis‐free response, sensitivity, and CO deactivation resistance. [ 66 ] This system also exhibited long‐term stability during operation under severe CO poisoning conditions, and no sign of deactivation after more than 50 H 2 pulses and more than 12 h in a 500 ppm CO background.…”
Section: Discussion Of Previous Workmentioning
confidence: 99%
“…It has been shown that these disadvantages can be overcome by alloying [17,18]. Specifically, the introduction of about 20% of gold (Au) suppresses the phase transition, making the response of the sensor a linear function of hydrogen pressure [6,17,[19][20][21]. To optimize these systems for hydrogen sensing, important questions remain: in what proportions should we mix the two alloyants, what shapes should the NPs have, and what features of the optical response should the sensing mechanism be based on?…”
Section: Introductionmentioning
confidence: 99%
“…In thermodynamic equilibrium and in the absence of hydrogen, bulk Pd-Au is expected to form an alloy without longrange order and at most a low degree of short-range order [25,26]. Furthermore, since in many studies the nanoalloys are annealed at high temperatures [6,17,21], it is safe to assume that the chemical distribution of the alloyants is close to random. To represent this situation in our calculations, we use special quasi-random structures (SQSs) [27], which are constructed to reproduce the (lack of) short-range order in a truly random alloy using unit cell sizes that are small enough for efficient calculations (in our case 24 Au/Pd atoms and 0-24 H atoms).…”
Section: Introductionmentioning
confidence: 99%